Peningkatan Pemahaman Karakteristik Financial Technology terkait Pinjaman Online di Kalangan Wanita Katolik Lingkungan Santa Maria Regina di Kota Surakarta: Increasing Understanding of Financial Technology Characteristics Related to Online Loans Among Catholic Women in the Santa Maria Regina Neighborhood in Surakarta City - Tsary, Syifa Rana; Indrastuti, Lusia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Technological developments have an impact on aspects of human life. One of them is in the economic sector. Initially, people applied for conventional loans through financial institutions or financial institutions, but now it is made easier with the presence of financial technology platforms. The convenience offered in online loan applications is a double-edged sword; if people lack understanding, it could result in them being caught in a case. This service aims to provide information and insight regarding the characteristics of legal fintech so that people avoid things that are detrimental to them. The method used in this community service consists of three stages: preparation, implementation of legal counseling, and evaluation, which are done by holding a post-test. As for the results of this community service, initially, the audience needed help understanding the difference between legal and illegal fintech; now, they can differentiate between the two and are more careful when applying for loans or receiving online loan offers.